Development of an agenda for research and action on climate change and health in the Caribbean - Saria Hassan; Calae Philippe; Renée M. West; Shelly McFarlane; Karen Polson-Edwards; Georgiana Gordon-Strachan; C. James Hospedales; Robert Dubrow; Caroline F. Allen (Revista Panamericana de Salud Pública)
This paper delineates the development of the Caribbean Research for Action Agenda which aims to empower Caribbean Small Island Developing States to reduce their vulnerabilities to the effects of climate change on health. The Caribbean Research for Action Agenda emerged from collaboration between nongovernmental organizations, academic institutions, and multilateral agencies that organized a conference on climate change and health in the Caribbean. This Agenda was formulated by prioritizing research areas, synthesizing evidence from conference presentations and scientific literature, and holding consultations with stakeholders and experts. The Agenda provides information on 18 priority areas for research and action categorized into four domains: climate change health impacts, exposures, and vulnerability; adaptation, planning, and resilience for health; mitigation actions and health co-benefits; and resources and engagement for climate change and health action. Cross-cutting findings underscore the need for: greater public and professional awareness; a more climate-literate health workforce; interdisciplinary collaboration to address institutional silos; attention to social and economic mediating factors; equitable interventions for vulnerable groups; and enhanced monitoring and surveillance of climate-sensitive health outcomes. The Caribbean Research for Action Agenda is a foundational tool to inform research, guide multisectoral collaboration and capacity-building, develop evidence-based policy, and inspire community action-based advocacy related to climate change and health.